The role of youth in the development of the state in the context оf globalization (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This article examines the issue of the place of youth in the development of the state, taking into account the ongoing political, economic, and social processes in the world. Based on the results of a partial study, ways of more effective interaction between government agencies and youth representatives are proposed. An attempt has been made to find solutions to the problems of modern youth in the Kyrgyz Republic.
Keywords: youth, state, country, world, world community, time, social networks, Internet